1999
DOI: 10.1099/00221287-145-10-2757
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of gas vesicle genes in Planktothrix rubescens from Lake Zürich

Abstract: ) shows that strains of the GV3 genotype produce gas vesicles with a higher critical pressure than those of GV1 and GV2. A PCR survey of 185 clonal cultures of P. rubescens isolated from Lake Zu $ rich revealed that 3 isolates were of genotype GV1, 73 were of GV2 and 109 were of GV3. The PCR technique was used to distinguish the gas vesicle genotype, and thence the associated critical-pressure phenotype, of single filaments selected from lakewater samples. Sequence analysis of the 16S rDNA and of regions withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(139 citation statements)
references
References 31 publications
4
135
0
Order By: Relevance
“…In these calculations we used the growth-rate coefficients for Pla 9316 rather than those for Pla 9303 (Table 1) ; a recent survey has shown that filaments with the same genotype (GV2) as strain Pla 9316 were commonly found in Lake Zu$ rich, whereas those with the same genotype (GV1) as Pla 9303 were rarely encountered (Beard et al, 1999). The potential growth rates for each depth and time on the first day of the study, 10 July 1995, were calculated by transferring the data on I Z \I !…”
Section: Calculations On Growth Of Planktothrix In Lake Zuw Richmentioning
confidence: 99%
“…In these calculations we used the growth-rate coefficients for Pla 9316 rather than those for Pla 9303 (Table 1) ; a recent survey has shown that filaments with the same genotype (GV2) as strain Pla 9316 were commonly found in Lake Zu$ rich, whereas those with the same genotype (GV1) as Pla 9303 were rarely encountered (Beard et al, 1999). The potential growth rates for each depth and time on the first day of the study, 10 July 1995, were calculated by transferring the data on I Z \I !…”
Section: Calculations On Growth Of Planktothrix In Lake Zuw Richmentioning
confidence: 99%
“…The deduced amino acid product of ORF1 (151 residues) is similar to the N-terminal part of GvpC 20 of Planktothrix rubescens BC-Pla 9316 (Beard et al, 1999). Parts of ORF2, designated gvpC1 0 and gvpC2 0 (Fig.…”
Section: Identification Of the Gvpacnj Gene Cluster Of Arthrospira Spmentioning
confidence: 99%
“…The newly designed Arthrospira primers are indicated by their respective letters and numbers, but the prefix ArGVP (see Table 1) is omitted. Primers U5 0 and U3 0 correspond to the universal degenerate gvpA primers GVPA-5 0 and GVPA-3 0 of Beard et al (1999), respectively. The sequence of this 1683-bp region was obtained by sequencing clone D1683 (Supplementary Table 1).…”
Section: Sequencing and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations